2009
DOI: 10.1103/physrevlett.102.081101
|View full text |Cite
|
Sign up to set email alerts
|

Signals of the QCD Phase Transition in Core-Collapse Supernovae

Abstract: We explore the implications of the QCD phase transition during the postbounce evolution of corecollapse supernovae. Using the MIT bag model for the description of quark matter and assuming small bag constants, we find that the phase transition occurs during the early postbounce accretion phase. This stage of the evolution can be simulated with general relativistic three-flavor Boltzmann neutrino transport. The phase transition produces a second shock wave that triggers a delayed supernova explosion. If such a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
364
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(377 citation statements)
references
References 37 publications
12
364
0
1
Order By: Relevance
“…Pons et al 2001;Popov et al 2006;Blaschke et al 2013b) and simulations of core-collapse supernovae (cf. Sagert et al 2009;Fischer et al 2011;Nakazato et al 2014). It is therefore of paramount interest to develop quark-hadron hybrid models from which it is possible to deduce observables that allow us to further constrain the as yet highly uncertain QCD phase diagram, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Pons et al 2001;Popov et al 2006;Blaschke et al 2013b) and simulations of core-collapse supernovae (cf. Sagert et al 2009;Fischer et al 2011;Nakazato et al 2014). It is therefore of paramount interest to develop quark-hadron hybrid models from which it is possible to deduce observables that allow us to further constrain the as yet highly uncertain QCD phase diagram, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…At these densities, hyperons, kaons, and quarks, if they appear at all, should not play a dominant role [46]. However, their possible appearance in a first order phase transition could be probed in the neutrino signal of a galactic supernova explosion [47,48]. In Fig.…”
Section: Implications Of the Nuclear Symmetry Energy On Radii Anmentioning
confidence: 99%
“…Several groups have previously studied the possibility of forming a quark core in CCSNe [9][10][11]. These studies typically make use of spherically symmetric general relativistic radiation hydrodynamics and Boltzmann neutrino transport.…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear matter equation of state (EOS) is modified to include a quark phase -a hybrid EOS such as the combination of HShen and Bag Model EOS's. For example, it was reported that for a progenitor mass of 10.8 M⊙ and Bag constant B 1/4 = 162 MeV, the quark phase transition occurs at relatively low density, resulting in a second collapse of the core triggering a delayed shock, at hundreds of ms after the prompt collapse [10,11].…”
Section: Introductionmentioning
confidence: 99%